2015
DOI: 10.1039/c5ta05334j
|View full text |Cite
|
Sign up to set email alerts
|

A bi-functional metal-free catalyst composed of dual-doped graphene and mesoporous carbon for rechargeable lithium–oxygen batteries

Abstract: Mesoporous carbon on nitrogen and sulfur co-doped graphene nanosheets (NSGC) was synthesized and its bi-functional catalytic activity toward oxygen reduction reaction and oxygen evolution reaction was investigated. The NSGC material showed high bi-functional catalytic activity due to the synergistic effect of co-doping of sulfur and nitrogen, as well as the presence of a hierarchical porous structure. The enhanced bi-functional catalytic activity of NSGC facilitated the efficient formation and decomposition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 50 publications
(91 reference statements)
0
44
0
6
Order By: Relevance
“…With the aid of LiI as a redox mediator, Liu et al have recently demonstrated a high capacity (typically between 25 000 to 40 000 mAh g À1 ), comparable to the theoretical value of Li-O 2 batteries, for a RGO framework electrode. [113] In this case, the mesoporous structure can accommodate the insoluble Li 2 O 2 formed during discharge. [113] In this case, the mesoporous structure can accommodate the insoluble Li 2 O 2 formed during discharge.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…With the aid of LiI as a redox mediator, Liu et al have recently demonstrated a high capacity (typically between 25 000 to 40 000 mAh g À1 ), comparable to the theoretical value of Li-O 2 batteries, for a RGO framework electrode. [113] In this case, the mesoporous structure can accommodate the insoluble Li 2 O 2 formed during discharge. [113] In this case, the mesoporous structure can accommodate the insoluble Li 2 O 2 formed during discharge.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…65 They found that the N and S dual-doped graphene has better catalytic activity on ORR than only N-doped graphene, probably due to the synergistic effect of dual-doping and superiority of S than N with two lone-paired electrons. The improved electrocatalytic activity caused by N and S atoms paves the way of practical application of NSG in the Li-air batteries, as demonstrated by Kim et al 66 The electrochemical performance of NSG reported in recent years is summarized in Table 2.…”
Section: N B-doped Graphenementioning
confidence: 96%
“…[110] Als Kathode in einem Li-O 2 -System zeigte dieses Material eine gute Entladungsrate mit einer spezifischen Entladungskapazität von 1280 mAh g À1 selbst bei einer hohen Stromdichte von 200 mA g À1 . [113]. Copyright 2011 American Chemical Society).…”
Section: Aufsätzeunclassified
“…c) Hochauflçsende TEM-Aufnahme von NSGC, die die mesoporçse Morphologie auf der rGO-Oberfläche zeigt. [113] [113].…”
Section: Aufsätzeunclassified
See 1 more Smart Citation